2019
DOI: 10.1038/s41598-019-42292-w
|View full text |Cite
|
Sign up to set email alerts
|

Long intergenic non-coding RNAs regulate human lung fibroblast function: Implications for idiopathic pulmonary fibrosis

Abstract: Phenotypic changes in lung fibroblasts are believed to contribute to the development of Idiopathic Pulmonary Fibrosis (IPF), a progressive and fatal lung disease. Long intergenic non-coding RNAs (lincRNAs) have been identified as novel regulators of gene expression and protein activity. In non-stimulated cells, we observed reduced proliferation and inflammation but no difference in the fibrotic response of IPF fibroblasts. These functional changes in non-stimulated cells were associated with changes in the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 65 publications
2
24
0
Order By: Relevance
“…Specifically, in obese subjects we found several lncRNAs (e.g., ZFAS1, LUCAT1, HIF1A-AS1, HOXB-AS3) already identified in the setting of different type of cancers, but not previously reported in human AT. Moreover, the lncRNA MIR3142HG, recently described as important mediator of the inflammatory response in Idiopathic Pulmonary Lung Fibroblasts positively regulating CXCL8 and CCL2 release (68), is specifically up-modulated in obesity. Notably, we previously reported an upregulation of both CCL2 and CXCL8 in adipocytes from Ob individuals (29), suggesting a role of this lncRNA in the AT inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, in obese subjects we found several lncRNAs (e.g., ZFAS1, LUCAT1, HIF1A-AS1, HOXB-AS3) already identified in the setting of different type of cancers, but not previously reported in human AT. Moreover, the lncRNA MIR3142HG, recently described as important mediator of the inflammatory response in Idiopathic Pulmonary Lung Fibroblasts positively regulating CXCL8 and CCL2 release (68), is specifically up-modulated in obesity. Notably, we previously reported an upregulation of both CCL2 and CXCL8 in adipocytes from Ob individuals (29), suggesting a role of this lncRNA in the AT inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…LINC01140 and LINC0090 were also found to be upregulated in isolated IPF fibroblasts, and LINC01140 was also upregulated in IPF biopsies and was shown to be a negative regulator of the inflammatory response [84]. Knockdown studies have also demonstrated that both lncRNAs play a role in mediating proliferation with and without PDGF-stimulation in both control and IPF fibroblasts.…”
Section: Long Non-coding Rnas Linc01140 and Linc0090mentioning
confidence: 94%
“…As well as biopsies, gene expression in isolated human lung fibroblasts has also been employed to examine and identify novel IPF-related genes and pathways. A recent microarray study identified several IPF-associated genes upregulated in both lung control and IPF fibroblasts in response to TGF-β1 [84]. Another study by Lee et al, identified CCL8 expression to be elevated in IPF lung fibroblasts using microarrays [43].…”
Section: Gene Expression Studies In Ipfmentioning
confidence: 99%
“…An up-to-date study revealed that the upregulation of certain lincRNAs, namely LINC00960 and LINC01140, and knockdown of LINC01140 but not LINC00960, stimulates the inflammatory response in IPF fibroblasts. Thus, demonstrating the importance of lincR-NAs as regulators of proliferation and inflammation in IPF for the first time [15]. Dai et al [16] found that the lncRNA MALAT1 could activate the lipopolysaccharide-induced inflammatory response pathway and promote the progression of lung injury in rat models.…”
Section: Lncrnas Are Involved In Ipf Through the Inflammation-immunementioning
confidence: 98%